THE FORMATION OF CONFLICTOLOGICAL COMPETENCE OF A HIGH SCHOOL TEACHER - Irina NIKULINA; Natalya SOLOVOVA (Высшее образование в России)
Abstract. This article discusses the process of formation of conflictological competence of a University teacher. There have been analyzed the interpretation of the concept of "conflictological competence of a University teacher", presented in the literature. The structure of conflictological competence of a teacher of the University is described, consisting of interrelated components: Gnostic; regulatory; engineering; reflexive and status; regulatory; communicative. There have been considered the conditions that must be created for the process of formation of conflictological competence of heads of educational units, teachers to be more effective. The methods and forms of formation of conflictological competence of a University teacher are described. There are presented the training program "Technology of conflict management in educational institutions" aimed at the formation of conflictological competence of heads of educational units and educational-thematic plan programs of advanced training "Management of pedagogical conflict", aimed at the formation of University teachers competencies for the constructive resolution of pedagogical conflicts.